Respuestas

  • Usuario de Brainly
2013-11-12T02:01:49+01:00
-4y+5x  por -3x + 2y
(-4y + 5x)( -3x + 2y) =              aplicando propiedad distributiva
+ 12yx - 8y² - 15x² + 10xy =
- 8y² - 15x² + 22xy

8n-9m  por 4n+6m
(8n -9m)(4n +6m) =
32n² + 48nm - 36mn - 54m²=
32n² + 12mn - 54m²

x3-2x2 +3x-1 por 2x +3
(x³ - 2x² + 3x - 1)( 2x + 3)=
2x^4 + 3x³ - 4x³ - 6x² + 6x² + 9x - 2x - 3 =
2x^4 - x³ + 0x² + 7x - 3
2x^4 - x³ + 7x - 3

3y3+5-6y por y2+2

(3y³ +  5 - 6y )( y² + 2) =
3y^4 + 6y³ + 5y² + 10 - 6y³ - 12y =
3y^4 + 0y³ - 7y² + 10 =
3y^4 - 7y² + 10

espero que te sirva, salu2!!!!!